LEVEL OF KNOWLEDGE AND IMPLEMENTATION OF CATTLE BARN BIOSECURITY RELATED TO PREVENTION OF FOOT AND MOUTH DISEASE IN GIANYAR BALI - Nurlastri Natalia; I Ketut Suada; Tri Komala Sari (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Foot and mouth disease is a disease that attacks cloven-hoofed animals, one example of which is cattle. Foot and mouth disease makes many farmers lose money so vaccination is carried out to prevent it. However, this alone is not enough, to prevent this, the Ministry of Agriculture advises farmers to tighten biosecurity. The aim of this research was to determine the level of knowledge of livestock breeders and cowshed biosecurity regarding the prevention of foot and mouth disease in Gianyar Regency, Bali. The data collection technique was carried out by random purposive sampling in each group. Each group represents two people from each simantri group. Then the data was analyzed descriptively qualitatively and displayed in table form and using a 0-2 Likert scale, to find a relationship between the level of knowledge and biosecurity implementation, the data was analyzed using a correlation test. From the interview results, it was obtained that simanteri in Gianyar Regency had knowledge with a percentage of 58% or in the sufficient category. Knowledge is influenced by several factors, namely education, age and length of maintenance. In this research, the higher the education, the better the knowledge they have, but this does not apply to the level of age and length of maintenance, the longer the age or the length of maintenance does not determine whether the simantri have good knowledge. This is one of the reasons why Simanteri does not implement biosecurity properly. The implementation of biosecurity standards in Gianyar Regency, Bali is in the poor category with an average score of 11.3 or equivalent to 37.6%. There are still many people who have not implemented cage biosecurity. In the correlation test, knowledge only affects 0.601, and the rest is influenced by many factors that need to be investigated further. From the correlation test, the strength of the relationship between knowledge and attitudes of breeders is considered very weak. However, the relationship between the two variables is unidirectional, where if knowledge simultaneously increases, biosecurity implementation will also increase. Based on the research results, the author suggests carrying out additional outreach and education efforts.